Formação pedagógica de professores de uma universidade pública baiana: teares, linhas e tessituras - Ramos, Evódio Maurício Oliveira (2014)
Dissertative this work, developed in the Graduate Program in Education , State University of Feira de Santana - Bahia , we analyze , from the representations of teachers participating in the experience of teacher training : teaching and learning , Learning and Evaluation in Higher Education , the changes occurring in their educational practice . Initially , we present the scenario of expansion of higher education , the legal basis of performance and training needs of university professors . We then describe some experiences of teacher training and present a review of literature on the production of dissertations and theses from CAPES , in order to understand the advances in research on university teaching and possible gaps . In Theoretical Framework , we point briefly , the political landscape of teacher education in Brazil , the context of university teaching and the relationship between teacher identity and professionalism to then describe some models of teacher training ( education model based on analysis practices and reflection , education model for methodological work or didactic work , Model inquiring or research training and continuing education model for didactic- pedagogic update) . The research methodology is based on the principles of the Social Representations Theory ( SRT) , characterized as a descriptive, qualitative character. The research group was composed of 06 faculty members who participated UEFS the last class of the course mentioned above , and a teacher trainer . The procedure of collecting and compiling the data used was the semistructured interview and the chosen method of analysis , thematic analysis of Bardin (1977 ) . In the presentation and discussion of the data , 03 categories were identified : the first related to participating teachers ( teacher identity , teacher training and training needs ) ; The second , related to the course ( origin, epistemological concept , teaching strategies , encouraging the institution , difficulties and setbacks ) ; and third , the ongoing contributions to pedagogical practice ( socialization among teachers in student learning , the innovative experiments in the evaluation process and the weaknesses and suggestions made by teachers ) . In the conclusion , we list some aspects that denote the importance of this training experience , including : epistemological reflections of teachers on their practices , innovations in teaching strategies , personal and professional growth, to improve the academic activities and better understanding of act of teaching and learning.